Safety and efficacy of low-dose and long-course tirofiban in large hemispheric infarction - Hu, Yinqin; Xiao, Qian; Shi, Zhizhen; Hou, Yangbo; Chen, Zhen; Cheng, Jiwei; Li, Guoyi (Frontiers in Neurology, 2022)
Background: The clinical efficacy and safety of tirofiban in the treatment of large hemispheric infarction (LHI) remains controversial. Methods: This study prospectively enrolled patients with acute LHI who were admitted to Putuo Hospital affiliated with Shanghai University of Traditional Chinese Medicine from June 2021 to December 2021. The patients were randomly assigned to the tirofiban group (3-4 µg/(kg·h)) or control group (clopidogrel 75 mg/d). Results: A total of 71 patients with acute LHI were selected: 36 in tirofiban group and 35 in control group.The reduction of the NIHSS score in tirofiban group was 2.92±9.31 at discharge, and that of the control group was -3.23±12.06 (P=0.021, OR, 0.006; 95% CI, 0.004-0.008). Six patients (16.7%) in tirofiban group and 14 patients (40%) in control group died during hospitalization (P=0.029, OR, 0.300; 95% CI, 0.099-0.908). There was significant difference in mRS 5-6 scores at 90 days between the two groups (P=0.023, OR, 0.327; 95% CI, 0.124-0.867). However, there was no significant difference in mRS 0-1 (P=0.321, OR, 0.972; 95% CI, 0.920-1.027), mRS 2 (P=0.572, OR, 2.00; 95% CI, 0.173-23.109), mRS 3 (P=0.225, OR, 2.214; 95% CI, 0.601-8.161) or mRS 4(P=0.284, OR, 1.859; 95% CI, 0.593-5.825) scores between the two groups. There was no difference in symptomatic intracranial hemorrhage (P=0.29, OR, 0.305; 95% CI, 0.030-3.081) , asymptomatic intracranial hemorrhage (P=0.123, OR, OR, 0.284; 95% CI, 0.053 - 1.518). There was significant difference in systemic bleeding events during hospitalization (P=0.044, OR, 0.309; 95% CI, 0.096-1.000). Conclusions: Low-dose and long-course tirofiban treatment may significantly improve the early neurological function and reduce the in-hospital mortality in LHI patients. Meanwhile, tirofiban does not increase the risk of any type of bleeding events.